Grain Quality of Three Rice Genotypes Grown in Organic and Non-Organic Systems - Dulbari, Dulbari; Kartahadimaja, Jaenudin; Martina, Ajeng Aulia; Santosa, Edi (Department of Agronomy and Horticulture, IPB University, 2024)
Grain quality is essential for assessing the overall quality of the grain produced and determining the market value of the final product. The objective of this study was to evaluate the physical quality of grains cultivated using both organic and non-organic methods. The research employed grains from red, white, and black rice genotypes planted during the third period. Each sample consisted of 100 grams, with three replicates. Data analysis involved variance testing using T and BNT tests, with a significance level set at 5%. Parameters for assessing the physical quality of grains included moisture content, empty grains, damaged kernels (yellow), calcified kernels (young kernels), foreign matter, other varieties, odors, and pests. The research took place at the Polytechnic Organic Farm and Plant Laboratory of Politeknik Negeri Lampung from January to April 2022. The findings indicated that the grain yields of red, white, and black rice genotypes quantitatively exhibited lower levels of yellow/damaged kernels and calcified/young kernels when cultivated organically compared to non-organic methods. However, for other analyses, the results did not show significant differences between the two cropping systems. Nevertheless, the grains of red, white, and black rice genotypes met the quality standards outlined in SNI 01-0224-1987, classified as grade II for organic cultivation and grade III for non-organic cultivation.